A study of epitaxial growth behaviors of equiaxed alpha phase at different cooling rates in near alpha titanium alloy. (1st January 2017) - Gao, Xiongxiong; Zeng, Weidong; Zhang, Saifei; Wang, Qingjiang
Abstract: The epitaxial growth behaviors of equiaxed primary α phase (αp ) at different cooling rates (150–0.15 °C/s) in a near α titanium alloy Ti60 were studied by optical micrograph, back scattered electron (BSE) images, high-resolution electron backscatter diffraction technique (EBSD) and electron probe microanalysis (EPMA). Microstructural observations indicated that the size of αp significantly increased with decreasing cooling rate. The rim-α phase observed by BSE image, which formed at the periphery of αp during cooling and has an identical crystallographic orientation to the interior region of αp analyzed by Kikuchi diffraction patterns, is considered to be evidence of epitaxial growth of αp . EBSD analysis also showed that αp preferentially grew extending for a distance along the β/β boundary resulting in extension-α phase from αp . The EPMA confirmed that contrast difference in BSE image within αp is caused by the difference in composition. The further microanalysis of local composition indicated that epitaxial growth during continuous cooling is mainly controlled by the diffusional redistribution of aluminum and molybdenum atoms between αp and β matrix. On this basis, the sizes of αp were theoretically calculated after continuous cooling based on a diffusion-controlled model, and model predictions showed good agreement with experimental measurements. Graphical abstract: Image 1